An Outcome Evaluation of a Substance Abuse Program for Probationers: Findings from a Quasi-Experimental Design - Hollis, Meghan E.; Jennings, Wesley G.; Hankhouse, Shannon (American journal of criminal justice, 2019)
The current study provides an evaluation of a substance abuse treatment program for probationers in a county in the state of Texas. Relying on a quasi-experimental design with a propensity score matched sample of 69 treatment group subjects and 69 control group subjects, the results revealed that while a significant treatment effect was observed for program participants in terms of a reduction in recidivism, a significant treatment effect on the percentage of people failing drug tests or the rate of failed drug tests was not detected. Study limitations and implications are also discussed.